Strategi Pendidikan dalam Membangun Kesejahteraan Anak di Tengah Dinamika Sosial Budaya dalam Persepektif Empiris di Era Inklusi - Syifa’u Rohmah; Risbon Sianturi; Taopik Rahman; Hamizah Mas’udah; Gina Nafisa Qurrota’ayun; Rifdah Devi Dzhihni (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to examine educational strategies in promoting children's well-being amid socio-cultural dynamics in the era of inclusion. Children's well-being is not limited to physical aspects, but also includes emotional, social, and psychological dimensions that are interconnected. Ongoing socio-cultural changes, including technological developments and shifting patterns of social interaction, have influenced children's growth and development. Therefore, educational approaches need to move beyond academic achievement and address children's holistic needs. This research employs a qualitative approach using a literature review method from various relevant sources. The findings indicate that effective educational strategies to support children's well-being include the implementation of social-emotional learning, differentiated instruction, and the creation of inclusive and supportive learning environments. In addition, the roles of family, school, and community are crucial in fostering children's overall well-being